Analisis Etika Berkomsumsi Pada Makanan dan Minuman : (Studi Mahasiswa Mahasiswi Fakultas Ekonomi Dan Bisnis Islam Prodi Ekonomi Syariah UIN Sulthan Thaha Saifuddin Jambi ) - Habriyanto Habriyanto; Laily Ifazah; Desi Pratiwi (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
This research is about the analysis of ethical consumption of food and drinks (Study of students from the Islamic Economics and Business Faculty, Sharia Economics Study Program, UIN Sulthan Thaha Saifuddin Jambi). This research aims to find out more about the ethical patterns of student food and drink consumption and Islamic economic views regarding student food and drink consumption. The method used by researchers is a qualitative method. The object of this research is students majoring in sharia economics, FEBI Class of 2019-2020. The data sources used are primary and secondary data using data collection techniques in the form of observation, interviews and documentation. The results of this research show that students' consumption ethics in fulfilling food or primary blindness (dhuriyat) are seen from the type of food they consume, the way they consume it and the quantity of food they consume is not fully in accordance with consumption ethics. In terms of ethics, most students do not pay attention to ethics and manners in consuming and from the five principles of Islamic consumption there is a gap between theory and practice. Based on the principle of simplicity, students consume excessively which can lead to wastage and waste. Meanwhile, students' moral principles do not follow the rules of etiquette and ethics set out by the Prophet Muhammad SAW. Most students do not apply this principle. Judging from the way they eat, they don't pay attention to consumption ethics based on what the prophet taught, and their habit of often throwing away rice and then leaving the environment dirty because they don't clean the place immediately after they consume food.